NEW CHALLENGES DURING THE PANDEMIC: PSYCHOLOGICAL UNDERDSTANDING - Natalia, Zhyhaylo; Nataliya, Bozhenko; Ostapiwna, Kokhan Marianna; Ihorovich, Bozhenko Myroslav; Olga, Bianco (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to presentation of the relevance of issues caused by the latest problem of the global pandemic. The fact that people from different countries, of different age, with different social status, level of material security, found themselves in similar, complex, undefined and unpredictable circumstances, was psychologically cognized; they all to a greater or lesser extent feel their vulnerability and insecurity. Modern circumstances are described, when a person faces deprivation of his/her psychological, social, spiritual and other needs, when you are under the threat to experience either a great or minor loss - from temporary unemployment to a prolonged recession; from the mild case of the disease to fatal consequences. Such circumstances are a probable predictor of the development of anxiodepressive reactions or clinical depression that has pronounced clinical symptoms, including depressed mood, appetite and sleep disorders, loss of interest, apathy, suicidal thoughts. The article presents a reassessment of the spiritual values of the individual, in particular, his/her attitude to happiness. It is proved that only under the condition of professional and spiritual formation and realization of personality it is possible to achieve the life goal - happiness; that there is no future without education and teachers, there is no future without health and doctors, there is no future without spirituality and God. The level of anxiety and depression of the respondents was studied. The program of spiritual values development was proposed as a technique to successfully stop the state of uncertainty, depression and find a way to achieve desired happiness.